Hospital Central Laboratory's Manpower Planning by Use of Queueing Theory - Brahma, Prasanta Kumar (Prabandhan: Indian Journal of Management, 2010)
The function of the technicians in a hospital central laboratory is to collect the samples and to investigate these samples under the supervision of specialist doctors and prepare the report. When ever a patient arrives, the samples are collected by the technician of the sample collection counter and after that, he sends those samples to different departments of the central laboratory such as Pathology, Biochemistry and Microbiology etc.. After receiving the samples the technician of the concerned departments process those samples under the supervision of the specialist doctors and prepares the reports. The service facility is arranged in parallel; as in Fig.-1: technicians M1, M2, M3 etc. may be facilities, and incoming patients are served by any free technician. If no technician is free, patients must wait and may thus accumulate, forming a queue. Patients are usually all given the same priority, so that service is on a first come first served basis.